E-Comic Media and Cognitive Profile in Learning Proclamation History: Media E-Comic dan Profil Kognitif dalam Pembelajaran Sejarah Proklamasi - Novitasari Novitasari; Nur Aeni Marta; Nurzengky Ibrahim (Academia Open, 2025)
Background: The integration of digital media in education has grown significantly, with e-comics emerging as an engaging alternative to conventional teaching tools. Specific Background: In history education, traditional media such as PowerPoint may not sufficiently stimulate student engagement or accommodate diverse cognitive abilities. Knowledge Gap: Limited empirical evidence exists regarding the interplay between e-comic media and students' critical thinking abilities in influencing learning outcomes. Aims: This study investigates the impact of e-comic media and critical thinking ability on history learning outcomes among class XI students at SMAN 84 West Jakarta. Results: Using a 2x2 factorial design and two-way ANOVA, findings reveal a significant difference in learning outcomes between students taught with e-comics and those with PowerPoint, favoring the former. However, no direct effect of critical thinking ability alone was observed. Importantly, a significant interaction effect between media type and critical thinking ability was identified. Novelty: The study demonstrates that the effectiveness of e-comic media is moderated by students’ critical thinking levels—both low and high-level thinkers benefit more from e-comics compared to PowerPoint. Implications: These findings suggest that e-comic media can serve as an effective and adaptive instructional tool in history education, supporting differentiated learning strategies. Highlights: Demonstrates e-comics' superior effectiveness over PowerPoint. Reveals interaction between media type and critical thinking ability. Supports differentiated instruction using adaptive digital tools. Keywords: E-Comic Media, Critical Thinking, History Learning, Learning Outcomes, Experimental Study